A prática da mentoria no desenvolvimento de pessoas nas organizações - Silva, Katline de Fátima Fortes (2008)
This study aimed to answer the question: what justifies the practice of mentoring and how it relates to the learning of technical abilities and interpersonal? To answer this question, we use literature research, and the field, through the implementation of an open questionnaire. The literature search allowed us to identify the mentoring as a process in which the mentor invests their time providing a technical support and personnel, acting as adviser of mentored, and this process leads to the development of people. Moreover, starting from the assumption that mentoring can be identified as a process to support individual learning. The results of the field research pointed the positive influence that process for people in organizations. Given the advantages pointed out by respondents of the questionnaire, identified the motives for this practice. Moreover, the respondents affirmed that the mentoring can be considered a resource of learning of technical abilities and interpersonal.